Prevalence of Malnutrition and Feeding Difficulties in Children With Esophageal Atresia. Issue 4 (April 2017) - Menzies, Jessica; Hughes, Jennifer; Leach, Steven; Belessis, Yvonne; Krishnan, Usha
ABSTRACT: Objectives: Growth and feeding problems have been described in children with esophageal atresia (EA). Ongoing gastrointestinal and respiratory complications such as Gastroesophageal reflux disease, esophageal dysmotility, strictures, and respiratory infections may contribute. The aim of the study was to document the prevalence of malnutrition and feeding difficulties and examine predictive factors, which may influence feeding and growth in children attending a multidisciplinary EA clinic in Sydney, Australia. Methods: A retrospective review of 75 children, ages 0 to 16 years, who attended a multidisciplinary EA clinic between 2011 and 2014. Data on demographics, comorbidities, nutrition, and mealtime behaviors were collected from their initial clinic appointment. Factors that may affect on growth and mealtime behaviors were identified and analyzed. Results: Nine percent of children were malnourished and 9% were stunted. Infants, children with prior fundoplication, at risk of aspiration, or those who had surgery in the first year of life additional to EA repair were significantly more likely to be malnourished ( P  < 0.05). Fifty-four percent of children required texture modification at their meals, with parental concern being the most common reason. Younger children were less likely to be eating age-appropriate textures ( P  = 0.04) which improved after 5 years of age. Conclusions: Poor growth and inability to manage age-appropriate textures are often present in children with EA, particularly in the younger years. This highlights the need for early intervention in a specialist multidisciplinary EA clinic in which dietetics and speech pathology are available. Abstract : Supplemental Digital Content is available in the text